Influence of the uncertainties in the Solar Quiet Reference Field (SQRF) model for deriving geomagnetic indices over South America. (August 2021) - Chen, S.S.; Denardini, C.M.; Resende, L.C.A.; Chagas, R.A.J.; Moro, J.; Silva, R.P.; Carmo, C.S.; Picanço, G.A.S.
Abstract: In this work, we present the uncertainties of the empirical model developed to predict the solar quiet regular daily field variation (Sq) over the Brazilian sector called the Solar Quiet Reference Field (SQRF) model. The SQRF is based on the magnetic station records from the Embrace Magnetometer Network (Embrace MagNet) during the solar cycle 24. Although the prediction and the magnetic field records have a good agreement, we observe that each magnetic station shows a random error behavior, propagating small errors in the model. Also, some physical aspects, as tidal winds and ionospheric conductivity, may have influenced our predictions. Thus, these uncertainties in the Sq field can propagate errors and influence geomagnetic indices' calculation by erroneously scaling the geomagnetic disturbances. In this context, we introduce a new approach to derive a 'real-time' geomagnetic index based on the SQRF model for the Sq-H field over the South American sector. We analyze one geomagnetic storm event to show that the results have a good representation of the geomagnetic indices. Finally, this analysis yields a new approach to derive the geomagnetic index for space weather applications and studies that requires an Sq field prediction. Highlights: Uncertainties of the empirical Sq field model are described and evaluated for deriving geomagnetic indices in South America. Geomagnetic indices are derived for the South American sector using the Embrace MagNet data. The geomagnetic indices derived using the predicted SQRF model present a lower mean error and RMSE than the standard real-time method.